2010
DOI: 10.1007/s00044-010-9494-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anti-inflammatory and analgesic activity of 3-[(5-substituted-1,3,4-oxadiazol-2-yl-thio)acetyl]-2H-chromen-2-ones

Abstract: A novel series of 3-[(5-substituted-1,3,4-oxadiazol-2-yl-thio)acetyl]-2H-chromen-2-one (7a-i) were synthesized by the condensation between the appropriately substituted 5-substituted-1,3,4-oxadiazolyl-2-thione (4a-i) derived from various existing NSAIDs and 3-(2-bromoacetyl)-2H-chromen-2-one (6) under reflux in the presence of sodium ethoxide. Structure of the synthesized compounds was established on the basis of physicochemical, elemental analysis, and spectral data. The title compounds were screened for in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…(The scheme was redrawn from literature.) [33][34][35][36][37][38][39][40][41] ChemistrySelect ChemistrySelect formation of 1,3-thiazolidine-2,4-dione-coumarin compounds (21) in potassium carbonate and dimethylformamide solution in reasonable-to-good yields (Scheme 3). [41] The antioxidant, anti-inflammatory and antidiabetic activity of synthesized compounds were evaluated and in cases for R = 4-Cl, 3-Br, 3-OC 2 H 5 -4-OH displayed the best activities in vivo.…”
Section: Nucleophilic Substitutions Of 3-bromoacetylcoumarinmentioning
confidence: 99%
See 1 more Smart Citation
“…(The scheme was redrawn from literature.) [33][34][35][36][37][38][39][40][41] ChemistrySelect ChemistrySelect formation of 1,3-thiazolidine-2,4-dione-coumarin compounds (21) in potassium carbonate and dimethylformamide solution in reasonable-to-good yields (Scheme 3). [41] The antioxidant, anti-inflammatory and antidiabetic activity of synthesized compounds were evaluated and in cases for R = 4-Cl, 3-Br, 3-OC 2 H 5 -4-OH displayed the best activities in vivo.…”
Section: Nucleophilic Substitutions Of 3-bromoacetylcoumarinmentioning
confidence: 99%
“…For instance, the reaction of 3‐bromoacetylcoumarin ( 2 ) with heterocyclic amines under reflux conditions formed amino acetyl compounds ( 3 ) in good yields [33] . A series of oxadiazol‐2‐ylthio‐acetyl‐2 H ‐chromen‐2‐ones ( 5 ) were made in reasonable‐to‐good yields by the condensation of 3‐bromoacetylcoumarin ( 2 ) and oxadiazolyl‐2‐thione ( 4 ) with sodium ethoxide as a catalyst under reflux conditions in ethanol [34] . Compounds 5 were evaluated in vivo for acute anti‐inflammatory and analgesic activities at a dosage of 200 mg/kg bw and considerable anti‐inflammatory and analgesic activity were reported (c, e, f and h) [34] …”
Section: Nucleophilic Substitutions Of 3‐bromoacetylcoumarinmentioning
confidence: 99%
“…Inflammation is a physiological reactionwhich involves cellular and biochemical responses, which is not only symptom for common diseases but also known to be an early phase for some serious diseases such as alzheimer's disease, cancer, heart vascular diseases [ 1 ] etc. Nonsteroidal anti-inflammatory drugs (NSAIDs) like ketoprofen, ibuprofen, aceclofenac, and so forth under current clinical usage for the treatment of inflammation, algesia and pyresis [ 2 ] are associated with major drawbacks of gastrointestinal disorders like dyspepsia, gastric ulcers, and so forth, due to the direct contact of free carboxylic group with the gastric mucosa [ 3 , 4 ] and due to decrease in production of prostaglandins in tissue [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Bhandari et al, (2008) reported the synthesis and pharmacological evaluations (antiinflammatory, analgesic, and ulcerogenicity) of novel Schiff bases derived from 2-[(2,6-dichloroanilino) phenyl] acetic acid (Diclofenac). Based on the above mentioned facts and in continuation of our research program (Palkar et al, 2014;Ingale et al, 2012;Khode et al, 2009;Gadad et al, 2008) on the synthesis of novel therapeutic antiinflammatory agents, we herein report the synthesis and spectral studies of series of novel Schiff base analogs derived from a versatile phenylalanine scaffold (2a-j). These compounds exhibited an interesting anti-inflammatory and analgesic activity profile with significant reduction in their ulcerogenic effect.…”
Section: Introductionmentioning
confidence: 99%